2002
DOI: 10.1515/ijmsp.2002.4.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Model for Predicting Surface Finish of Machined UNS A92024 Alloy Bars

Abstract: In this work, a study on the dry turning process of UNS A92024 alloy has been carried out. This study has been achieved on the basis of the analysis of the surface finishing of the machined pieces in terms of roughness parameter, R a , as a function of cutting speed, v, and feed, f. The aim of this work has been devoted to establish R a =R a (v,f) parametric relations. Two steps have been followed in order to obtain these relations.Thus, in a first step, R a (v) and R a (f) potential curves have been fitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The experimental results suggest that it is possible to obtain a potential parametric model of X = f(v c , f, a p ) with a better fit than other models. This was in accordance with the statistical treatment proposed for similar studies [ 27 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 92%
“…The experimental results suggest that it is possible to obtain a potential parametric model of X = f(v c , f, a p ) with a better fit than other models. This was in accordance with the statistical treatment proposed for similar studies [ 27 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 92%
“…Previous research has shown the limited influence of the cutting depth ( ) on GD obtained when these alloys are machined [34,37,51,59]. Due to this, its value remained constant in tests performed, with value of = 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Potential models, similar to (1), usually show a good fit for aeronautical aluminum alloys. In this regard, some researchers suggest removing the cutting depth from (1), due to its small influence on Ra, in machining of UNS A92024 (Al-Cu) and UNS A97050 (Al-Zn) alloys [37,59].…”
Section: Introductionmentioning
confidence: 99%
“…Previously to performing the tests, the surface of the cylindrical workpieces were roughdressed by a high feed horizontal turning process in order to remove the surface deposits formed in the storing period. After this, a latter surface finishing small-feed turning process was carried out in order to avoid chattering effects on the workpiece surface [9].…”
Section: Experimental Procedures and Materialsmentioning
confidence: 99%